ADVANCING STUDENTS FROM B1 TO C1 LEVEL IN FOUR FUNDAMENTAL LANGUAGE SKILLS : EFFECTIVE METHODS AND STRATEGIES - Bekmurodova Maftuna Jumanazar qizi; Xurshidova Madina Jasur qizi (Western European Studies, 2024)
This article delves into effective methodologies and strategies for elevating students from B1 to C1 proficiency in the four fundamental language skills: reading, writing, listening, and speaking. The progression from intermediate to advanced language competence necessitates a multifaceted approach, incorporating both traditional and innovative teaching techniques. This paper examines the efficacy of immersive learning environments, task-based activities, and the integration of authentic materials to enhance comprehension and production skills. It underscores the significance of personalized feedback, formative assessments, and collaborative learning in promoting language acquisition. Furthermore, the article explores the utilization of digital tools and multimedia resources to create dynamic and engaging learning experiences. By synthesizing current research and practical applications, this study provides educators with actionable insights and strategies to effectively guide their students towards achieving advanced language proficiency.
Keywords: Language proficiency; Reading skills; Writing skills